The effects of substituting deproteinized whey or pure lactose for dried whey on starter pig performance - Nessmith, W.B. Jr.; Bergstrom, J.R.; Smith, J.W.II; Owen, K.Q.; Loughmiller, J.A.; Musser, R.E.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A study was conducted to evaluate the effects of replacing all or half of spray-dried, edible-grade whey with deproteinized whey or pure lactose on starter pig performance. No differences in pig performance were observed. Therefore, high quality deproteinized whey and lactose are effective replacements for the lactose provided by dried whey in starter pig diets.
Keywords: Swine; Starter; Whey; Lactose; Performance